2022
DOI: 10.1039/d2qo00474g
|View full text |Cite
|
Sign up to set email alerts
|

Phenanthrene[2]arene: synthesis and application as nonporous adaptive crystals in the separation of benzene from cyclohexane

Abstract: Phenanthrene[2]arene 1 with excellent adsorption capacity for benzene was synthesized in high yield. Activated crystals of 1 have been successfully used to separate PhH from equimolar mixture of PhH and Cy and the purity of the PhH can reach 98.4%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 35 publications
1
19
1
Order By: Relevance
“…Although, the synthesis of host 1 (ref. 46 ) have been reported by our group recently. However, we found that the synthetic route can be further optimized to synthesis of the precursor 3, which is beneficial to the subsequent large-scale production.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…Although, the synthesis of host 1 (ref. 46 ) have been reported by our group recently. However, we found that the synthetic route can be further optimized to synthesis of the precursor 3, which is beneficial to the subsequent large-scale production.…”
supporting
confidence: 55%
“…Similar to the phenanthrene[2]arene as the nonporous adaptive crystals for benzene adsorption capacity, 46 activated host 1 was prepared by recrystallization in the mixture of CH 2 Cl 2 /MeOH and dried under vacuum at 150 °C for 6 h. To study the selectivity of p X over m X , single-component solid–vapor sorption experiments were first performed with the activated solid of 1 toward p X and m X . The mole ratio of time-dependent solid–vapor sorption plots were determined by the 1 H-NMR analysis.…”
mentioning
confidence: 99%
“…We questioned whether the intense fluorescence of the benzothiadiazole-based cage would increase compared to the monomers. Herein, as a continuation of our interest for supramolecular chemistry [ 45 , 46 , 47 , 48 , 49 ], we report a turn-on fluorescent probe based on a self-assembled cage for the selective detection of Cd 2+ . The self-assembled cage 1 was obtained by the condensation of 4,4′-(benzothiadiazole-4,7-diyl)dibenzaldehyde and TREN in chloroform via the [3 + 2] approach ( Scheme 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…13 Very recently, our group also developed a system featuring fast adsorption, high loading ratios, high purity, and easy recycling for the separation of PhH and Cy by using phenanthrene[2]arene. 14 Chromatography is one of the most efficient ways to separate complex mixtures. However, the application of synthetic macrocyclic compounds in chromatography has rarely been explored.…”
Section: Introductionmentioning
confidence: 99%